(untitled) (Global Journal of Human-Social Science, 2012)
This article will discuss the history of religious tolerance its definitions and experience of Malaysian society The brief discussion of the history of toleration starts from the Cyrus the Great of Persia 500 years BCE until this century Then it continues with the debate on the definitions of tolerance The discussion follows by exploring everyday life of the Malaysian society in which it seems that there are contradictory situations happen in Malaysia From one pole there are evidence of a highly tolerated society whereby from the other pole the situation is totally opposite